Assessment of posttensioned concrete beams from the 1940s: Large‐scale load testing, numerical analysis and Bayesian assessment of prestressing losses. (10th February 2021) - Botte, Wouter; Vereecken, Eline; Taerwe, Luc; Caspeele, Robby
Abstract: The UCO textile factory was built in Ghent (Belgium) in the period 1947–1948. The roof structure covered an area of about 35, 000 m 2 and consisted of 100 primary beams and 600 secondary beams. These post‐tensioned beams were designed by prof. Gustave Magnel, who was a world‐leading expert in the field of prestressed concrete. This project was one of the first important large‐scale applications of prestressed concrete in industrial buildings in the world and also the first large scale application of on site prefabrication. Recently, part of the factory building was demolished and a primary beam and secondary beam of the roof structure were transferred to the Magnel‐Vandepitte Laboratory for Building Materials and Structures for testing at an age of approximately 70 years. The primary beams have a span of 20.5 m and a maximum depth of 1.7 m. The secondary beams have a span of 13.7 m and a depth of 1 m. Only prestressing tendons (Blaton–Magnel system with Ø 5 mm wires) were present in the beams but no passive reinforcement nor stirrups are present except for the reinforcement in the corbels and the end blocks. This article describes the results of the loading tests up to failure on the beams. The experimental results are compared with results from analytical calculations. Furthermore, a nonlinear finite element model was developed and validated. Subsequently, this numerical model was used for a Bayesian‐based assessment of the prestressing losses in these beams. As such, the article presents novel information related to time‐dependent prestress losses after 70 years in service as well as the structural performance of such existing post‐tensioned concrete structures dating from that pioneering period.